2010
DOI: 10.1242/jeb.028365
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the potential for vascular bubble formation in a repetitively diving dolphin

Abstract: SUMMARYThe production of venous gas emboli (VGE) resulting from altered dive behavior is postulated as contributing to the stranding of beaked whales exposed to mid-frequency active sonar. To test whether nitrogen gas uptake during repetitive breath-hold diving is sufficient for asymptomatic VGE formation in odontocetes, a bottlenose dolphin (Tursiops truncatus Montagu) was trained to perform 10-12 serial dives with 60s surface intervals to depths of 30, 50, 70 or 100m. The dolphin remained at the bottom dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 59 publications
(91 reference statements)
4
42
1
Order By: Relevance
“…Our resting f H was significantly lower (41±8 beats min −1 ) than values from previous studies in the awake, unrestrained (60-105 beats min −1 ; Houser et al, 2010;Noren et al, 2004;Williams et al, 1993) or anesthetized bottlenose dolphin (84-140 beats min −1 ; Sommer et al, 1968). The most likely explanation is our conservative approach in estimating f H and SV exclusively after cardiac frequency had stabilized in between breaths.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Our resting f H was significantly lower (41±8 beats min −1 ) than values from previous studies in the awake, unrestrained (60-105 beats min −1 ; Houser et al, 2010;Noren et al, 2004;Williams et al, 1993) or anesthetized bottlenose dolphin (84-140 beats min −1 ; Sommer et al, 1968). The most likely explanation is our conservative approach in estimating f H and SV exclusively after cardiac frequency had stabilized in between breaths.…”
Section: Discussioncontrasting
confidence: 65%
“…In cetaceans, no published data exist on cardiac contractile responses during forced or voluntary dives, with most studies being largely focused on cardiac frequency (Houser et al, 2010;Noren et al, 2004). One study measured CO in anesthetized bottlenose dolphins (Sommer et al, 1968), but the experimental artifacts of mechanical ventilation under general anesthesia and restraint out of water may have altered normal physiological function, so these data may have to be viewed with caution when compared with awake individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Houser and colleagues have recently re-visited the question of nitrogen saturation in the bottlenose dolphin Tursiops truncatus and concluded that nitrogen supersaturation is likely. However, they were unable to demonstrate vascular bubble formation in a repetitively diving trained animal (Houser et al 2010).…”
Section: Introductionmentioning
confidence: 93%
“…These instruments yield very reliable solubility measurements and are still in use today (e.g. Houser et al, 2010); however, their use is somewhat limited as so few remain in existence. The empirical studies that have been carried out on lipids (for reviews, see Langø et al, 1996;Weathersby and Homer, 1980) indicate that manufactured oils of different biochemical composition have different N 2 solubility coefficients (e.g.…”
Section: Introductionmentioning
confidence: 99%